Modulation of Microtubule Dynamics Affects Brucella abortus Intracellular Survival, Pathogen-Containing Vacuole Maturation, and Pro-inflammatory Cytokine Production in Infected Macrophages - Alves-Silva, Juliana; Tavares, Isabela P.; Guimarães, Erika S.; Costa Franco, Miriam M.; Figueiredo, Barbara C.; Marques, João T.; Splitter, Gary; Oliveira, Sergio C. (Frontiers in Microbiology, 2017)
The microtubule (MT) cytoskeleton regulates several cellular processes related to the immune system. For instance, an intricate intracellular transport mediated by MTs is responsible for the proper localization of vesicular receptors of innate immunity and its adaptor proteins. In the present study, we used nocodazole to induce microtubules depolymerization and paclitaxel or recombinant (r) TIR (Toll/interleukin-1 receptor) domain containing protein (TcpB) to induce microtubule stabilization in bone marrow-derived macrophages infected with Brucella abortus. Following treatment of the cells, we evaluated their effects on pathogen intracellular replication and survival, and in pro-inflammatory cytokine production. First, we observed that intracellular trafficking and maturation of Brucella-containing vesicles (BCV) is affected by partial destabilization or stabilization of the MTs network. A typical marker of early BCVs, LAMP-1, is retained in late BCVs even 24 hours after infection in the presence of low doses of nocodazole or paclitaxel and in the presence of different amounts of rTcpB. Second, microscopy and CFU analysis revealed that bacterial load was increased in infected macrophages treated with lower doses of nocodazole or paclitaxel and with rTcpB compared to untreated cells. Third, innate immune responses also were also affected by disturbing MT dynamics. MT depolymerization by nocodazole reduced IL-12 production in infected macrophages. Conversely, rTcpB-treated cells augmented IL-12 and IL-1β secretion in infected cells. In summary, these findings demonstrate that modulation of microtubules affects several crucial steps of B. abortus pathogenesis, including BCV maturation, intracellular survival and IL-12 secretion in infected macrophages.